GUÍAS PARA DIAGNÓSTICO, PREVENCIÓN Y TRATAMIENTO DE LA OSTEOPOROSIS 2007 - Schurman, León; Bagur, Alicia; Claus-Hermberg, Haraldo; Messina, Osvaldo Daniel; Negri, Armando; Sanchez , Ariel (Actualizaciones en Osteología, 2024)
-